FAKTOR PENENTU PARTISIPASI SEKOLAH ANAK PADA RUMAH TANGGA SEKTOR PERTANIAN DI INDONESIA - Diyang Gita Cendekia (Research Centre for Population, Indonesian Institute of Sciences, 2020)
The opportunity of demographic dividend is the biggest motivation in improving the quality of the population. As one of the components of the population quality, education is also a long-term investment. Economic activities in Indonesia depends on the agricultural sector. This study aims to determine the determinants of children's school participation in agricultural households. Using the 2018 National Social and Economic Survey data, the results of binary logistic regression analysis show that economic activity has the most significant contribution to determine children's school participation in agricultural households. Children in agricultural households who are not involved in economic activities tend to attend school. Other important factors in determining children's school participation in agricultural households are government assistance, the age of household heads (KRT), education of KRT, employment status of KRT, number of household members, residence area, and socio-economic status. Increasing the determinants of school participation is expected to help the population adapt to the technology-based modern agricultural sector and achieve prosperity in agricultural households.